Auditoría operativa y su incidencia en los procesos de compras públicas de la estación experimental tropical Pichilingue del iniap, Cantón Mocache, Período 2023-2024 - Peña Carranza, Cristina Verónica (2025)
This study analyzes the impact of the operational audit on the public procurement processes of the Pichilingue Tropical Experimental Station of INIAP, Mocache canton, during the period 2023-2024. Through a descriptive, field and applied research, supported by inductive, deductive and analytical methods, regulatory compliance, operational efficiency and institutional budget management were evaluated. It was found that, although the entity generates contract files in accordance with current legal regulations, there are still shortcomings in the follow-up and closing of processes in the Official Public Procurement System, affecting traceability and accountability. Structural delays were also identified as a result of weaknesses in the planning of the Annual Procurement Plan, delays in budget certifications and late delivery of terms of reference by the operating units. These factors have limited the timely fulfillment of research requirements, generated risks of budget under-execution and affecting the achievement of institutional goals. Despite achieving high levels of budget execution (96.27% in 2023 and 92.81% in 2024), as a result, there is evidence of over-execution in the operational and control plans due to the lack of formal control mechanisms and continuous follow-up, which compromises the efficiency of public spending. Consequently, the importance of strengthening operational auditing as an essential tool for improving contracting processes and optimizing the use of public resources is reaffirmed.